E-közigazgatás és agrár-szakigazgatás Magyarországon - Nagy, Elemérné; Hampel, György; Fabulya, Zoltán (Jelenkori Társadalmi és Gazdasági Folyamatok, 2008)
The aim of our paper is to give an overview of the electronic public administration and the agrarian administration in Hungary. The size of the administration affects economic growth: it consumes 35 to 49 percent of the GDP in the European countries. By introducing electronic services, more than 5 percent of the administration costs can be saved. The efforts to digitize are based on the e-Europe programme with the objective to create an information society for everyone. After creating the legislative background in the past years, administration offices could digitize their registry and could start to offer more and more electronic services to the citizens and organizations. Although the level of digital literacy should be raised among the citizens and the civil servants as well, Hungary can be proud of the quality of the electronic administration services which is above the EU-28 average. The agrarian administration needs a lot of data which is collected and processed by information systems obligatory in the European Union. The collected data is required to effectively operate the agriculture and to access European agricultural subsidies. In the past few years efforts were made to catch up with the European agrarian information systems and today these systems are able to provide the necessary information for the administration and the farmers as well.